Peran Maternal Self-Efficacy sebagai Mediator terhadap Mindfulness dan Postpartum Depression pada Ibu Primipara - Yantina, Maisi; Roswiyani, Roswiyani; Sahrani, Riana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Primiparous mothers, women who are giving birth for the first time, face challenges in adapting to a new postpartum role as a mother. Due to the pressure they are under, they are more likely to suffer from psychological issues including anxiety and depression. The purpose of this study is to ascertain how maternal self-efficacy affects mindfulness and postpartum depression in primiparous mothers. This study utilized a correlational quantitative approach with 295 primiparous mothers ranging in age from 20 to 42 years. The Dinni-Difa Postpartum Scale (DDPS) from Ardiyanti and Dinni (2018), Tarumanagara Five Aspect Care Survey (TFFMQ) developed by Baer et al . (2006) and Perceived Maternal Parental Self-Efficacy (PMP S-E) from Barnes and Adamson-Macedo's (2007) were used to collect data on postpartum depression (PPD), mindfulness, and maternal self-efficacy (MSE) in primiparous mothers. When analyzing the data, the Pearson product moment correlation test was combined with the PROCESS by Hayes for SPSS regression test for hypothesis testing. According to the analysis's findings, PPD is predicted by mindfulness, therefore with a lower risk of mothers experiencing PPD associated with higher levels of mindfulness. Mindfulness also significantly predicts MSE. However, MSE has not been demonstrated to serve as a mediator in the relationship between mindfulness and postpartum depression in primiparous women (ab = 0.016, BootLLCI = -0.011, BootULCI = 0.032).